2D VIDEO GAME DESIGN AND DEVELOPMENT USING FINITE STATE MACHINE METHOD - Diny Anggriani Adnas; Deren Deren (Universitas Internasional Batam, 2022)
Ever since the creation of world’s first video game named “Tennis for Two” by a physicist named William Higinbotham with a purpose of stimulate learning and interest in physic, a lot of researcher started to research the effectiveness of video game as an educational media. One of the research by Richard E. Mayer shown that Celeste Pilegard has already suggested the idea of video game as a homework material. But a lot of researcher said that they wanted an evidence of the effectiveness of video game as educational purposes. The research conducted by Richard E. Mayer said that video game can be used as educational purpose even surpass the conventional media. Python is an object-orientated programming language created by Guido van Rossum with a philosophy to make user able to read source code easier. This programming language is popular to the point a lot of companies uses Python to create an application for their own company, because of this a lot of beginners wanted to study this language but struggle because of the difficulty of finding a free learning media for this programming language. The purpose of this research is to make the basic knowledge of Python Programming Language become even more accessible to everyone and to show the capability of the author in computer science department, specifically in video game development. The author uses Unity, Paint.NET and Bolt Visual Scripting as the tool to develop the video game in this research. The end result of this research is a video game titled “The Room” that developed using Unity as game engine and Finite State Machine as the method.